The Dynamic Correlations Between Mass Media News and New Media News in Stock Market - Zhang, Zuochao; Zhang, Yongjie; Shen, Dehua (Frontiers in Physics, 2020)
In this paper we examine the dynamic correlations between mass-media news and new-media news as well as their reprints in Chinese stock market. We mainly find that: (1) there is significant postitive between the four types of news and the correlation is stronger for the one between reprints and their congener media news; (2) both the mass-media news and new-media news have significant positive auto-correlation. The new-media news and the reprints rely more on mass-media news. (3) both mass-media news and new-media news will make a positive reponse to the corporate events, but the new-media news including the new-media reprints react stronger than mass-media; (4) the results of dynamic correlation analysis indicate that there is a significant correlation between the four types of news over time. The correlation between mass-media news and new-media news is stronger when the stock market performs well. We attribute these results to the symbiotic relationship between mass media and new media in Chinese market, where mass media devotes to provide original news with high quality and new media transfers these numbers of news to more readers to attract more attention and discussion.